Fifty years young : products and processes the future of chemical engineering - Bridgwater, John (Cambridge University Press, 1996)
Chemical engineering is that discipline centrally concerned with the economic, safe, environmentally acceptable manufacture of materials of all types solid, liquid or gas. These can be made by chemical or biochemical means. Stemming from the oil and gas industries, we now have a discipline with methods of broad applicability.